2021
DOI: 10.1093/eurpub/ckab170
|View full text |Cite
|
Sign up to set email alerts
|

Association of perceived job security and chronic health conditions with retirement in older UK and US workers

Abstract: Background The relationship between job insecurity, chronic health conditions (CHCs) and retirement among older workers are likely to differ between countries that have different labor markets and health and social safety nets. To date, there are no epidemiological studies that have prospectively assessed the role of job insecurity in retirement incidence, while accounting for CHC trajectories in two countries with different welfare systems. We investigated the strength of the association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Though work participation provides financial security and may have a positive effect on health and health-related quality of life, people with chronic health conditions are less likely to participate in the workforce, particularly if they are affected by more than one chronic health condition [5]. Furthermore, studies have revealed an increased risk of sick leave [6][7][8] and early retirement of employees with chronic conditions compared with people without a chronic condition [5,[9][10][11][12]. In Germany, almost one in five retirements is due to a health problem, with mental disorders, musculoskeletal disorders, cardiovascular diseases, and cancer accounting for almost 80 % of disability pensions [13].…”
Section: Introductionmentioning
confidence: 99%
“…Though work participation provides financial security and may have a positive effect on health and health-related quality of life, people with chronic health conditions are less likely to participate in the workforce, particularly if they are affected by more than one chronic health condition [5]. Furthermore, studies have revealed an increased risk of sick leave [6][7][8] and early retirement of employees with chronic conditions compared with people without a chronic condition [5,[9][10][11][12]. In Germany, almost one in five retirements is due to a health problem, with mental disorders, musculoskeletal disorders, cardiovascular diseases, and cancer accounting for almost 80 % of disability pensions [13].…”
Section: Introductionmentioning
confidence: 99%